Barcode-Karten as Learning Development to Improve Vocabulary Knowledge about German Language - Desti Nur Aini; Maura Safira Demara (Westscience Press, 2023)
The quality education process in learning foreign languages, mainly German, must be supported by learning media. To improve vocabulary knowledge about German Artikel with the Haustiere theme needs to be supported by